Influence of Service Quality and Delivery Speed on Customer Satisfaction in Logistics Business - Kholdun, Amrulloh Ibnu; Saribanon, Euis; Tantri, Roy Hartanto; Nap, Ferry Reynaldo Darmawan (Institut Transportasi dan Logistik Trisakti, 2023)
The purpose of this research is to measure whether there is any influence of service quality and delivery speed on customer satisfaction. This research employs a quantitative method using three variables: service quality and delivery speed as independent variables and customer satisfaction as dependent variable. The sample used in this research employed Probability Sampling Method utilizing Slovin formula, and was rounded to 100 respondents from buyer/end-users population of PT. XYZ (excluding seller/vendor users). Data analysis method used in this research is multiple linear regression analysis. Results from data analysis, T-Test and F-Test indicate: both service quality and delivery speed, individually and simultaneously, have positive influence on customer satisfaction. Hopefully, this research can provide insights into the impact of factors on customer satisfaction and guide companies in improving service strategies, enabling them to maintain and enhance customer satisfaction in the rapidly evolving e-commerce era through better services and faster delivery.